Antihypertensive Effect of Carica papaya Via a Reduction in ACE Activity and Improved Baroreflex - Brasil, Girlandia Alexandre; Ronchi, Silas Nascimento; do Nascimento, Andrews Marques; de Lima, Ewelyne Miranda; Romão, Wanderson; da Costa, Helber Barcellos; Scherer, Rodrigo; Ventura, José Aires; Lenz, Dominik; Bissoli, Nazaré Souza; Endringer, Denise Coutinho; de Andrade, Tadeu Uggere (Planta Medica, 2014)
The aims of this study were to evaluate the antihypertensive effects of the standardised methanolic extract of Carica papaya, its angiotensin converting enzyme inhibitory effects in vivo, its effect on the baroreflex and serum angiotensin converting enzyme activity, and its chemical composition. The chemical composition of the methanolic extract of C. papaya was evaluated by liquid chromatography-mass/mass and mass/mass spectrometry. The angiotensin converting enzyme inhibitory effect was evaluated in vivo by Ang I administration. The antihypertensive assay was performed in spontaneously hypertensive rats and Wistar rats that were treated with enalapril (10 mg/kg), the methanolic extract of C. papaya (100 mg/kg; twice a day), or vehicle for 30 days. The baroreflex was evaluated through the use of sodium nitroprusside and phenylephrine. Angiotensin converting enzyme activity was measured by ELISA, and cardiac hypertrophy was evaluated by morphometric analysis. The methanolic extract of C. papaya was standardised in ferulic acid (203.41 ± 0.02 µg/g), caffeic acid (172.60 ± 0.02 µg/g), gallic acid (145.70 ± 0.02 µg/g), and quercetin (47.11 ± 0.03 µg/g). The flavonoids quercetin, rutin, nicotiflorin, clitorin, and manghaslin were identified in a fraction of the extract. The methanolic extract of C. papaya elicited angiotensin converting enzyme inhibitory activity. The antihypertensive effects elicited by the methanolic extract of C. papaya were similar to those of enalapril, and the baroreflex sensitivity was normalised in treated spontaneously hypertensive rats. Plasma angiotensin converting enzyme activity and cardiac hypertrophy were also reduced to levels comparable to the enalapril-treated group. These results may be associated with the chemical composition of the methanolic extract of C. papaya, and are the first step into the development of a new phytotherapic product which could be used in the treatment of hypertension.
Keywords: baroreflex; ACE inhibition; flavonoids; quercetin; antihypertensive; Carica papaya; Caricaceae